Pengembangan Bahan Ajar Media Kahoot Untuk Pembelajaran PPKN Materi Keberagaman Kelas IV Sekolah Dasar - Sulistiawati Sulistiawati; Tita Mulyati; Yayang Furi Furnamasari (Jurnal Bintang Pendidikan Indonesia, 2023)
In research conducted at SDN Lojikobong II on learning Civics learning in elementary schools regarding diversity. In the current era, there are many problems that arise and the existing culture fades. The purpose of the research is to find out the design of teaching materials for learning PPKn, diversity material for grade IV elementary schools, the feasibility of teaching materials and user responses to kahoot teaching materials. This study uses the Design and Development model, namely D&D, with the design and development of Analysis, Design, Development, Implementation, Evaluation (ADDIE) research procedures. Media validation and kahoot learning materials use experts, namely media experts and material experts. The trials in this study were carried out by class teachers and students in class IV to obtain user responses. In this research, data collection techniques used questionnaires and interviews, research used media experts, material experts, teachers and students with instruments used questionnaires and interviews. The results of the study show that the assessment from the expert's point of view is in the very good category and the ratings from the users are very good. The recommendation from this study is that kahoot learning media can be used in the learning process with guidance on the use of teacher media and learning understanding of diversity material in students.